Overcoming barriers to implementing ward-based psychosocial interventions in acute inpatient mental health settings: A meta-synthesis. (March 2021) - Raphael, Jessica; Price, Owen; Hartley, Samantha; Haddock, Gillian; Bucci, Sandra; Berry, Katherine
Abstract: Background: The culture of acute mental health wards is often dominated by medical models of care despite some patient dissatisfaction with care in these settings and a demand for increased access to psychosocial interventions. Research has found that psychosocial interventions can improve a number of patient and staff outcomes, however, implementation within these settings is often challenging. Objectives: The aim of this review was to provide a comprehensive synthesis of the barriers and facilitators to implementing psychosocial interventions on acute wards, in order to develop a list of recommendations for embedding psychosocial interventions within the ward culture in acute settings. Methods: Databases were systematically searched using search terms related to acute mental health wards and psychosocial intervention implementation from inception to December 2019. Thirty-nine studies (forty-three papers) that explored the implementation of psychosocial interventions on adult acute mental health wards using qualitative methods met inclusion criteria. Data relating to barriers and facilitators to implementing psychosocial interventions extracted from the results sections of the papers were synthesised using the COM-B model. Results and conclusions: We conclude that to address barriers to the implementation of psychosocial interventions, services should provide clear information to patients regarding the benefits of engagement, and additional training for staff. A shift in ward culture is required and can be achieved through the recruitment of empathic implementers, together with providing staff with protected time for delivery of psychosocial interventions with clear accountability for intervention delivery through the provision of clearly defined roles.